Wear Evaluation of Nanostructured Ti Cermets for Joint Reconstruction. (September 2017) - Georgiou, E.P.; Drees, D.; Dosta, S.; Matteazzi, P.; Kusinski, J.; Celis, J.-P.
Abstract: Nanostructured cermet coatings consisting of titanium carbides dispersed in a titanium matrix were deposited by supersonic spraying. The aim is to develop novel wear resistant materials that can be applied in joint reconstruction. Structural analysis was performed by Scanning Electron Microscopy, Transition Electron Microscopy, and X-ray Diffraction, whereas the mechanical properties of each phase were determined by nanoindentation technique. In addition, in order to evaluate the friction and wear behavior of these Ti-TiC nanostructured cermet coatings, a two-step tribological approach was applied. This approach consists of two test series. First, pre-screening sliding wear tests were performed in order to provide a ranking of the coatings and a comparison with commonly used biomedical benchmarks. Subsequently parallel wear tests that simulate the joint contact conditions were used to evaluate the reliability of these coatings and the wear loss of the actual tribosystem (coatings vs polyethylene). The experimental results indicated that Ti-TiC cermets possess superior tribological properties, thanks to the appropriate balance of hard carbide and soft titanium phases, and the nanostructuring of the titanium matrix. The wear mechanism was investigated in order to establish a 'structure–property' relationship for these coatings. Highlights: Deposition of nanostructured cermets via supersonic spraying technique Microstructural analysis of Ti-TiC nanostructured sprayed coatings Tribological methodology for evaluating new biomaterials for reconstruction joints Statistical analysis of wear on UHMWPE countermaterial